Strategi Promosi Wisata Melalui Push Notification Smart Tourism Berbasis PWA di Pemandian Teluk Sibayan - Iqbal, Muhammad; Rohminatin, Rohminatin; Syahputra, Abdul Karim; Indriani, Meliya; Khairani, Alya Fauza (STMIK Royal, 2024)
The